HASIL KONFERENSI KEPENDUDUKAN DI KAIRO: IMPLIKASINYA PADA PROGRAM KESEHATAN REPRODUKSI DI INDONESIA - Siswanto Agus Wilopo (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1994)
The World PopulationConference in Cairo has received substantial attention and comments from the mass media and a large circle of experts, although a more basic explanation is still needed due to the result of the conference. Since abortion is considered a very important issue which dominates the field of reproductive health, it needs to further analyze the relations between abortion and the 'new concept' of reproductive health. This paper broadly analyzes the objectives and the agreed result of the conference. It also proposes several implications on the reproductive health program in Indonesia. Even though, as the mass media reported, the Cairo Conference seemed to be a conference on abortion, the theme of the conference was: Population, Sustainable Economic Growth, and Sustainable Development. Indonesia takes a very active role in the preparation of the world's population conference, including to conduct and initiate the summit population conference of the Non-Aligned Ministerial level prior the Cairo Conference. The Cairo World Population Conference has resulted in a substantially broad Population Action Program, in which the implementation needs serious consideration on the heterogeneity of the respective countries according to the priorities of development, cultural considerations, norms, religion, and law that prevails in the respective countries, yet the Conference should consider the norms of the universal human rights. Out of various materials covered in the Population Action Program, reproductive health problems have become one of the important controversial sources. For this reason it has thus been agreed to accept a